High intensity interval training vs. moderate intensity continuous training on aerobic capacity and functional capacity in patients with heart failure: a systematic review and meta-analysis - Yang, Changran; Zhang, Lizhuang; Cheng, Yu; Zhang, Manman; Zhao, Yuxin; Zhang, Tianzi; Dong, Jiawang; Xing, Jun; Zhen, Yuzhi; Wang, Cuihua (Frontiers in Cardiovascular Medicine, 2024)
Exercise training is commonly employed as a efficacious supplementary treatment for individuals suffering from heart failure, but the optimal exercise regimen is still controversial. The objective of the review was to compare the effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on the exercise capacity, cardiac function, quality of life (QoL) and heart rate among patients with heart failure with reduced ejection fraction.Methods: A systematic search was performed using the following eight databases from their inception to July 5, 2023: PubMed, Web of Science, Embase, Cochrane Library, Clinical Trials, China Knowledge Network, Wan fang Data, and the China Biology Medicine databases. The meta-analysis results were presented as mean difference (MD) and 95% confidence interval(CI). The Cochrane Risk of Bias tool was used for the included studies. The Grading of Recommendations Assessment, Development, and Evaluations was used to assess the certainty of evidence.Results: Thirteen randomized controlled trials were included in the study. The results showed that HIIT had a significant positive effect on peak oxygen uptake (MD=1.78,95% CI for 0.80 to 2.76), left ventricular ejection fraction (MD=3.13, 95% CI for 1.25 to 5.02), six-minute walk test (MD=28.13, 95% CI for 14.56 to 41.70), and Minnesota Living with Heart Failure Questionnaire (MD=-4.45, 95% CI for -6.25 to -2.64) compared to MICT. However, there were no statistically significant differences observed in resting heart rate and peak heart rate.Conclusions: HIIT significantly improves peak oxygen uptake, left ventricular ejection fraction, six-minute walk test, and Minnesota Living with Heart Failure Questionnaire in patients with heart failure with reduced ejection fraction. Additionally, HIIT exhibits greater effectiveness in improving peak oxygen uptake among patients with lower body mass index.